An Evaluation of Selected Basic Assumptions of the H. A. Wood Land Use Classification - Wobschall, Margaret (My University, 1973)
Two basic assumptions of the H. A. Wood Land Use Classification for the American Tropics are examined.
First, the nature of the relationship between the level of technology, climatic characteristics, economic output, and labour requirements is examined for individual crops using data acquired from the Ecuadorian government.
Second, the author examines the extent to which it is possible to separate, and accurately identify, the Wood Land Use Systems on aerial photographs. Photographs were interpreted from both the Sierra and coastal regions of Ecuador and later field checked by the author with the aid of the Ministerio de Agricultura.
Through analysis, certain assumptions of the classification have been verified, and some modifications have been suggested.
Keywords: Land Use; climatic characteristics; economic output; technology